Organizing and running winter triathlon competitions in Ukraine - Vladimir Vodlozerov (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to analyze the system of organizing and running competitions according to the type of the triathlon-winter program in Ukraine for compliance with the rules of the International Triathlon Federation. Material & Methods: on the basis of the study of the specialized literature and the regulatory framework of a number of triathlon federations, a comparative analysis of the winter triathlon emulation at competition distances abroad and in Ukraine. Result: correspondence of two winters combined distances in Ukraine to the official formats of the international winter triathlon competitions in Europe and the world are found out. Conclusion: in basis for organizing and conducting competitions for a new variety of continuous triathlon in our country are the rules of the International Triathlon Federation, and the competitive distances in the form of the triathlon-winter program in Ukraine correspond to international standards.